Pengaruh Modal Usaha dan Jumlah Pelanggan Terhadap Pendapatan Produsen Roti di Kota Denpasar dengan Lama Usaha sebagai Variabel Moderating - Dana Putra, I Kadek Sustiawan; Setyadhi Mustika, Made Dwi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 10, Oktober 2016 (pp. 1011 - 1167), 2016)
The informal sector is a type of employment that is less organized, not have protection by legal entities which have a small scale is more aimed at finding employment and income rather than profit. The informal sector also includes various business activities that do not have protection by law. One of the informal sector that is growing is the bread or bakery industry. This study aimed to determine the effect of capital, the number of customers with the old business as moderating variable to earnings bread producers in Denpasar. The research methods used were interviews, questionnaires and observations. This study used a technique purposive sampling with 64 samples of bread manufacturers in the city of Denpasar. The study states simultaneously and partial capital, the number of customers and old businesses have significant effect on earnings. While long effort is a moderating variable that amplified the effect of the capital and the number of subscribers to revenue bread producers in Denpasar.
Keywords: capital; the number of customers; old business; revenues bread producers